2018
DOI: 10.32805/ijhr.2018.1.2.13
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Peer Learning to Nursing Care Knowledge and Occupational Stress of the Novice Nurse

Abstract: Background. The transition period for novice nurses is the transition of roles as students become professional nurses. Conflict between expectations and the reality of the roles faced can cause stress. The peer learning learning model is a method of learning with peers that aims to develop skills, ways of thinking, solving problems, giving feedback and communicating with others. This study aims to determine the effect of peer learning on nursing care knowledge and work stress on novice nurses in hospital in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Similar to the research of Stone et al (2013) which found that peer learning methods and classical conventional methods were equally able to improve the ability of nursing students to develop skills, communicate and think critically, this study showed that peer learning methods helped to increase nurses' ability to interpret ABGs than classical methods. Thus, this supports the study of El-Sayed, Metwally, and Abdeen (2013) and Dwijayanto, Wijayanti and Supardi (2018) that peer learning methods give a more significant effect on increasing knowledge than conventional classroom methods.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to the research of Stone et al (2013) which found that peer learning methods and classical conventional methods were equally able to improve the ability of nursing students to develop skills, communicate and think critically, this study showed that peer learning methods helped to increase nurses' ability to interpret ABGs than classical methods. Thus, this supports the study of El-Sayed, Metwally, and Abdeen (2013) and Dwijayanto, Wijayanti and Supardi (2018) that peer learning methods give a more significant effect on increasing knowledge than conventional classroom methods.…”
Section: Discussionsupporting
confidence: 83%